Appendiceal taeniasis presenting like acute appendicitis - Sartorelli, A. C.; Silva, Marcia Guimarães da [UNESP]; Rodrigues, MAM; da Silva, R. J. (Springer, 2005)
A case of parasitic appendicitis caused by Taenia sp. in a 28-year-old woman from Brazil is reported. Histopathological data and a description of the helminthe found in the appendix lumen are presented.